Carbon footprint of textile throughout its life cycle: a case study of Chinese cotton shirts. (1st December 2015) - Wang, Chenxing; Wang, Lihua; Liu, Xinlei; Du, Chong; Ding, Ding; Jia, Jia; Yan, Yan; Wu, Gang
Abstract: The carbon footprint (CFP) reflects the greenhouse gases (GHGs) generated throughout the life cycle of a human activity or product, and is therefore an important tool for assessing and managing GHG emissions. At the level of an individual product, a carbon-labeling scheme that provides more information for consumers could play an important role in encouraging a shift to low-carbon consumption. China is the largest textile and garment producer and consumer in the world. Studying the carbon footprint of textiles is therefore important domestically, for the management of domestic greenhouse gas emission and, internationally, for the communication of carbon information and relevant trade negotiations. For establishing the product carbon labeling system in China, this paper constructed an operable and comparable CFP assessment method and framework at product level and presents a complete case for pure cotton shirts made in China. Based on investigations of several Chinese textile companies and the observation of every production sub-process, the system boundary and methods of assessing textile product CFP were established. We then estimated Chinese CFP conversion factors for relevant energy sources and materials, and calculated the actual CFP for the life cycle of a pure cotton shirt. The average CFP of a pure cotton shirt produced in China, throughout its life cycle, is estimated as 8.771 kgCO2 e. Of this, direct CFP is 0.347 kgCO2 e, whereas indirect CFP is much higher, at 8.423 kgCO2 e. The industrial production stage accounts for the highest proportion of the CFP, and overall production (including agricultural and industrial production) accounts for more than 90% of the total CFP. Approximately 96% of CFP throughout the product life cycle is indirect CFP, which is embedded in the use of energy and materials in each process. Within the industrial production stage, the transportation and weaving sub-processes account for nearly all the direct CFP (0.347 kgCO2 e). Energy consumption, especially of electricity, is the main contributor to the CFP of textile products. These results could facilitate comparison between different products, and for the same products from different producers, In order to reduce the CFP throughout the entire textiles sector. Highlights: Estimated average CFP for the life cycle of a pure cotton shirt was 8.771 kgCO2 e. The industrial production stage accounts for the highest proportion of CFP. Overall agricultural and industrial production represents more than 90% of CFP. Approximately 96% of CFP is indirect, embedded in energy and materials. Energy consumption, especially electricity, is the main CFP of textile products.